Frontiers of colonialism - Beaule, Christine D. (University Press of Florida, 2017)
For decades archaeologists have limited studies of frontiers and colonialism to a single polity, empire, or epoch. This has been especially true of historical archaeologists; but in this intriguing collection, Beaule assembles archaeologists from around the world to determine the commonalities and differences of colonialism across the self-imposed divide of contact v. pre-contact. The work considers the expanding frontiers of the Romans, Iroquois, Egyptians, Filipinos, and the more familiar Mayan and Incan empires. The goal of this volume is to expand the theoretical interpretations and perspectives to all archaeologists working in frontier/colonial contexts, not just those of the European empires.